The effect of porcine somatotropin (pST) on production parameters, carcass and meat quality characteristics of pigs - Swarts, Isane C. (Isane Chjarl) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2005.